Nanobiosensors Design Using 2D Materials: Implementation in Infectious and Fatal Disease Diagnosis - Nandita Singh; Daphika S. Dkhar; Pranjal Chandra; Uday Pratap Azad (Biosensors, 2023)
Nanobiosensors are devices that utilize a very small probe and any form of electrical, optical, or magnetic technology to detect and analyze a biochemical or biological process. With an increasing population today, nanobiosensors have become the broadly used electroanalytical tools for the timely detection of many infectious (dengue, hepatitis, tuberculosis, leukemia, etc.) and other fatal diseases, such as prostate cancer, breast cancer, etc., at their early stage. Compared to classical or traditional analytical methods, nanobiosensors have significant benefits, including low detection limit, high selectivity and sensitivity, shorter analysis duration, easier portability, biocompatibility, and ease of miniaturization for on-site monitoring. Very similar to biosensors, nanobiosensors can also be classified in numerous ways, either depending on biological molecules, such as enzymes, antibodies, and aptamer, or by working principles, such as optical and electrochemical. Various nanobiosensors, such as cyclic voltametric, amperometric, impedimetric, etc., have been discussed for the timely monitoring of the infectious and fatal diseases at their early stage. Nanobiosensors performance and efficiency can be enhanced by using a variety of engineered nanostructures, which include nanotubes, nanoparticles, nanopores, self-adhesive monolayers, nanowires, and nanocomposites. Here, this mini review recaps the application of two-dimensional (2D) materials, especially graphitic carbon nitride (g-C3N4), graphene oxide, black phosphorous, and MXenes, for the construction of the nanobiosensors and their application for the diagnosis of various infectious diseases at very early stage.